The philosopher's dog friendships with animals - Gaita, Raimond 1946- (Random House Trade Paperbacks, 2005)
"The philosopher Raimond Gaita has always been fascinated by animals--their obvious intelligence and disturbing brutality, their uncanny responsiveness to our moods and needs, and the deep feelings they elicit from us and seem to return. In this marvelous, luminous book, Gaita trains the lens of philosophy on the mystery and beauty of the animals he has known and loved. What does Gaita's dog, Gypsy, think about while she sits on her mat gazing out to sea for hours on end? How can we acknowledge that animals are sentient and yet deny that they have consciousness? Is it possible to love animals and still eat meat? In contemplating questions like these, Gaita weaves together inspiring, sometimes heartbreaking personal accounts with the reflections and analysis of a professional philosopher. In the end, he argues that love should be the essence of our bond with animals, the critical factor that guides how we treat them and think about their place in our world"--Page 4 of cover
"Originally published in Australia in 2002 by the Text Publishing Company"--Title page verso
Friends and companions -- For a dog? -- The philosopher's dog -- Sitting on her mat, gazing out to sea -- Gypsy is old now -- "The honour of corpses" -- The realm of meaning -- Stories, philosophy, and science -- "Poor living thing" -- Sacred places -- Arrogance? -- Creatureliness -- Human beings and animals
Keywords: Human-animal relationships / Moral and ethical aspects; Animal welfare / Moral and ethical aspects; Animal psychology; Dogs / Australia / Anecdotes; Animals / Australia / Anecdotes; Human-animal relationships / Australia / Anecdotes; Animals; Dogs; Human-animal relationships; Ethik; Philosophie; Tiere; Mensch; Freundschaft; Tierhaltung; Australia; Australien